HUBUNGAN KONSUMSI MEDIA RELIGIUS TERHADAP RELIGIUSITAS REMAJA MUSLIM (SURVEI PADA MAHASISWA UNIVERSITAS PARAMADINA DAN UNIVERSITAS ISLAM X DI JAKARTA) - Aan Rukmana (Jurnal Universitas Paramadina, 2014)
AbstractThis research is investigating the relationship between religiousmedia consumption and religiosity among youth. The research is based itsassumption on media cultivation effect theory. According to this theory,media consumption is correlated with audiences' perception about the world.The religiosity in this research is divided into two variables, the level ofreligiosity and the religiosity orientation (extrinsic and intrinsic orientation).The research use quantitative methodology and survey as the method of datacollection. Population is drawn from students at two universities,Universitas Paramadina and Universitas Islam X at Jakarta (sample size is600 respondents). The research found significant but very weak relationshipbetween religious media consumption and the level of religiosity ( p= 0,046,r= 0,083), significant and weak correlation between religious mediaconsumption and intrinsic religious orientation ( p = 0,008, r= 0,110), and nosignificant relationship between religious media consumption and extrinsicreligious orientation.